Structure-based discovery of a novel small-molecule inhibitor of TEAD palmitoylation with anticancer activity - Gridnev, Artem; Maity, Subhajit; Misra, Jyoti R. (Frontiers in Oncology, 2022)
The paralogous oncogenic transcriptional coactivators YAP and TAZ are the distal effectors of the Hippo signaling pathway, which play a critical role in cell proliferation, survival and cell fate specification. They are frequently deregulated in most human cancers, where they contribute to multiple aspects of tumorigenesis including growth, metabolism, metastasis and chemo/immunotherapy resistance. Thus, they provide a critical point for therapeutic intervention. However, due to their intrinsically disordered structure, they are challenging to target directly. Since YAP/TAZ exerts oncogenic activity by associating with the TEAD1-4 transcription factors, to regulate target gene expression, YAP activity can be controlled indirectly by regulating TEAD1-4. Interestingly, TEADs undergo autopalmitoylation, which is essential for their stability and function, and small-molecule inhibitors that inhibit this posttranslational modification can render them unstable. In this article we report discovery of a novel small molecule inhibitor of YAP activity. We combined structure-based virtual ligand screening with biochemical and cell biological studies and identified JM7, which inhibits YAP transcriptional reporter activity with an IC50 of 972 nMoles/Ltr. Further, it inhibits YAP target gene expression, without affecting YAP/TEAD localization. Mechanistically, JM7 inhibits TEAD palmitoylation and renders them unstable. Cellular thermal shift assay revealed that JM7 directly binds to TEAD1-4 in cells. Consistent with the inhibitory effect of JM7 on YAP activity, it significantly impairs proliferation, colony-formation and migration of mesothelioma (NCI-H226), breast (MDA-MB-231) and ovarian (OVCAR-8) cancer cells that exhibit increased YAP activity. Collectively, these results establish JM7 as a novel lead compound for development of more potent inhibitors of TEAD palmitoylation for treating cancer.